TMEM205 Is an Independent Prognostic Factor and Is Associated With Immune Cell Infiltrates in Hepatocellular Carcinoma - Rao, Jiawei; Wu, Xukun; Zhou, Xiaozhuan; Deng, Ronghai; Ma, Yi (Frontiers in Genetics, 2020)
Hepatocellular carcinoma (HCC) is the second leading cause of cancer-related death worldwide despite the availability of diverse treatment strategies. Much research progress has been made regarding immunotherapy but the effects remain unsatisfactory, highlighting the urgent need for novel immune-related therapy targets. In recent years, more and more studies have pointed out the associations between certain transmembrane (TMEM) family proteins and tumor progression, but the role of TMEM205 remains unclear. In this study, we analyzed the RNA-seq and clinical data of 371 patients from The Cancer Genome Atlas (TCGA) and found significantly differential expression of TMEM205 between normal and tumor tissue(P <0.001). that Llow TMEM205 expression was also found to be independently associated with poor overall survival (OS; p=0.032) and poor disease-specific survival (DSS; p=0.002) in multivariate Cox regression analyses. RNA-seq and clinical data from hepatocellular carcinoma patients in International Cancer Genome Consortium(ICGC) also showed significantly differential expression of TMEM205 (P <0.001)and association between low TMEM205 expression and poor survival(P <0.001). We also used the Estimate the Proportion of Immune and Cancer cells (EPIC) tool to estimate the proportions of various immune cells in the tumor tissues. A correlation analysis was conducted, and TMEM205 expression in tumor tissues was found to be significantly associated with the proportion of macrophages (Pearson r = 0.45, p<0.0001). A negative correlation was found between TMEM205 expression and M2 macrophage markers (CD163, EGR2, and MS4A4A) and between TMEM205 expression and regulatory T cell (Treg) markers (CCR8, STAT5B, and IL2RA), while a positive correlation was found between TMEM205 expression and the proportion of CD8+ T cells (Pearson r = 0.26, p<0.0001). In conclusion, TMEM205 might improve HCC patients’ prognosis by reducing the levels of immunosuppressive cells (M2 macrophages and Tregs) and facilitating the infiltration of cytotoxic T cells into the tumor microenvironment. Therefore, TMEM205 has potential as a prognostic biomarker and immunotherapy agent in combination therapy regimens for HCC.